THE EFFECTIVENESS OF THE SHOOTING TRAINING MODEL USING THE REPETITION METHOD IN BASKETBALL FOR AGED 12-14 YEARS - Mayangsuri, Sari Mariping; Pelana, Ramdan; Sulaiman, Iman (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
This study aims to determine the improvement of shooting skills in basketball games with the repetition method in basketball games for ages 12-14 years. This research was conducted from May-June 2023. The subjects in this study were 45 players aged 12-14 years. This research focuses on testing the effectiveness of developing a shooting technique training model with the repetition method, therefore the approach and method used in this study is a quantitative approach with a pre-experimental research design in the form of the one group pretest-posttest design. Data analysis used the inferential analysis was carried out using the T test, with a significance test (α) = 0.05. In the significant difference test with SPSS 16, the average value = 1.778 shows the difference from the results of the pre-test and post-test, df = 44, the results of t count = 11.212 > t table 1.680 (from n = 45) and p-value = 0.00 <0.05, which means there is a significant difference between before and after being treated with the basketball shooting training model with the repetition method. The conclusion is that the basketball shooting exercise model with the repetition method is effective and provides an increase in the shooting skills of children aged 12-14 years